Evaluation of Epigallocatechin-3-Gallate as a Radioprotective Agent During Radiotherapy of Lung Cancer Patients: A 5-Year Survival Analysis of a Phase 2 Study - Zhu, Wanqi; Zhao, Yalan; Zhang, Shuyu; Li, Xiaolin; Xing, Ligang; Zhao, Hanxi; Yu, Jinming (Frontiers in Oncology, 2021)
Background Previous analysis of the study (NCT02577393) had demonstrated the application of epigallocatechin-3-gallate (EGCG) could be safe and effective in the prevention and treatment of acute radiation esophagitis in patients with advanced lung cancer. EGCG seemed to improve the response rate of small cell lung cancer (SCLC) to radiotherapy in a subgroup analysis. This research continued to analyze the impact of EGCG application on cancer-radiation efficacy and patient survival. Methods All patients with SCLC in the NCT02577393 study were included. Patients were randomized into EGCG group or conventional therapy group as protocol. The primary endpoints of the study were radiation response rate and progression-free survival (PFS). Overall survival (OS) and the efficacy of EGCG in the treatment of esophagitis were assessed as secondary endpoints. Results A total of 83 patients with lung cancer in the NCT02577393 study were screened, and all 38 patients with SCLC were eligible for analysis. No significant differences with regard to baseline demographic and clinical characteristics were observed between the two groups. The objective response rate (ORR) was higher than that of conventionally treated patients (84.6 vs 50%, P = 0.045), while the median PFS and OS were not significantly prolonged. At data cut-off (1 January 2021), 5-year PFS was 33% with EGCG versus 9.3% with conventional treatment, and 5-year OS was 30.3% versus 33.3%, respectively. The mean adjusted esophagitis index and pain index of patients with EGCG application were lower than conventional treatment (5.15 ± 2.75 vs 7.17 ± 1.99, P = 0.030; 8.62 ± 5.04 vs 15.42 ± 5.04, P < 0.001). Conclusion The study indicates EGCG may alleviate some esophagitis-related indexes in SCLC patients exposed to ionizing radiation without reducing survival. However, this conclusion should be confirmed by further studies with large sample size.